Terson syndrome and leukemia: a case report - Lorenzi U (Dove Medical Press, 2014)
Umberto Lorenzi, Elisa Buschini, Antonio Fea, Federica Machetta, Federico Maria GrignoloOphthalmic Section, Department of Clinical Pathophysiology, University of Turin, Turin, Italy Abstarct: Terson syndrome is defined as intraocular hemorrhage associated with intracranial bleeding. This syndrome can occur in the event of intracranial hemorrhage or elevated intracranial pressure. To our knowledge, it has never been associated with chronic myeloid leukemia. A 45-year-old woman suffering from chronic myeloid leukemia was referred to our clinic with Terson syndrome after intracranial bleeding. We followed this patient for a year, performing visual acuity assessment, fundus examination, color retinography, and A-scan and B-scan ultrasonography. At presentation, her best-corrected visual acuity on the right was 20/63 and on the left was 20/320. In the right eye, retinoscopy showed blurring of the optic margins surrounded by retinal and preretinal hemorrhages, preretinal fibrosis of the optic disc along the vascular arcades, and perivascular retinal infiltrates. In the left eye, the optic disc was surrounded by retinal and preretinal hemorrhages, and massive fibrosis with hard exudates and severe preretinal hemorrhage were observed at the posterior pole. Roth spots and many circular hemorrhages were noted at the periphery of the retina. A-scan and B-scan ultrasonography did not show intraocular leukemic infiltration. The clinical picture remained stable over the following 12 months. In this patient, we observed the ophthalmoscopic features of chronic myeloid leukemia, but also coexistence of features typical of Terson syndrome. To our knowledge, no similar cases have been reported previously.Keywords: retinal disease, chronic myeloid leukemia, eye hemorrhage, intracranial hemorrhage